PERSPEKTIF MAHASISWA FMIPA UNIMED TENTANG WAWASAN NUSANTARA UNTUK MEMBANGUN RASA NASIONALISME - Rama Fahri; Maghfirahtun Zahira; Rindi Prameswari; Dinda Amanda; Elviana Br Barus; Oksari Anastasya Sihaloho (Journal Education and Government Wiyata, 2024)
This study aims to explore the perspectives of FMIPA UNIMED students regarding Wawasan Nusantara and how this concept plays a role in fostering nationalism. Wawasan Nusantara, as Indonesia's geopolitical and geostrategic outlook based on Pancasila and the 1945 Constitution, serves as a crucial tool in maintaining the unity of the Indonesian state and strengthening national identity amidst the challenges of globalization. A descriptive qualitative method was employed to provide an in-depth understanding of students' comprehension of Wawasan Nusantara and the challenges in its application. The results revealed that FMIPA UNIMED students recognize the importance of Wawasan Nusantara in building nationalism, although there are obstacles in its implementation among younger generations. Innovative education and the use of digital media were proposed as solutions to enhance understanding and application of nationalist values. In conclusion, Wawasan Nusantara is key to strengthening Indonesia’s national unity and fostering strong nationalism among the younger generation.